2006
DOI: 10.1126/science.1125731
|View full text |Cite|
|
Sign up to set email alerts
|

X-ray Fluorescence Spectrometry of Asteroid Itokawa by Hayabusa

Abstract: X-ray fluorescence spectrometry of asteroid 25143 Itokawa was performed by the x-ray spectrometer onboard Hayabusa during the first touchdown on 19 November 2005. We selected those data observed during relatively enhanced solar activity and determined average elemental mass ratios of Mg/Si = 0.78 +/- 0.09 and Al/Si = 0.07 +/- 0.03. Our preliminary results suggest that Itokawa has a composition consistent with that of ordinary chondrites, but primitive achondrites cannot be ruled out. Among ordinary chondrites,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 16 publications
5
50
1
Order By: Relevance
“…The recovered particles were carefully studied by the preliminary examination (PE) team, and the obtained results provide significant and unique information about the formation and evolution of meteorite parent bodies Nagao et al 2011;Nakamura et al 2011;Noguchi et al 2011;Tsuchiyama et al 2011;Yurimoto et al 2011). The mineral compositions and oxygen isotope ratios of the particles studied by the PE team are very similar to those of the equilibrated LL chondrites Yurimoto et al 2011), which match the spectroscopic observations by the Hayabusa spacecraft (e.g., Fujiwara et al 2006;Abe et al 2006;Okada et al 2006). These studies further suggested that Itokawa is made of reassembled fragments of the interior portions of a once larger asteroid at least 20 km in diameter (e.g., Nakamura et al 2011Nakamura et al , 2014 and thus represents only a small fraction of the original asteroid's mass.…”
Section: Introductionsupporting
confidence: 48%
“…The recovered particles were carefully studied by the preliminary examination (PE) team, and the obtained results provide significant and unique information about the formation and evolution of meteorite parent bodies Nagao et al 2011;Nakamura et al 2011;Noguchi et al 2011;Tsuchiyama et al 2011;Yurimoto et al 2011). The mineral compositions and oxygen isotope ratios of the particles studied by the PE team are very similar to those of the equilibrated LL chondrites Yurimoto et al 2011), which match the spectroscopic observations by the Hayabusa spacecraft (e.g., Fujiwara et al 2006;Abe et al 2006;Okada et al 2006). These studies further suggested that Itokawa is made of reassembled fragments of the interior portions of a once larger asteroid at least 20 km in diameter (e.g., Nakamura et al 2011Nakamura et al , 2014 and thus represents only a small fraction of the original asteroid's mass.…”
Section: Introductionsupporting
confidence: 48%
“…Compared to the mass density of ordinary chondrites (∼3.4 g/cm 3 ), which are the closest meteorite analog (Okada et al 2006), this indicates a porosity as high as 40-50%. Rubble attenuates strong stress pulses (Love et al 1993) and thus any impactor capable of resetting Itokawa's crater population must be large enough to cause global shaking despite the attenuation.…”
Section: Crater Erasure On Itokawamentioning
confidence: 81%
“…Both objects have almost identical geometric albedos: 0.29 ± 0.02 for Itokawa (Bernardi et al 2009) for Itokawa, well within the derived range for Apophis. Itokawa has a SIV-type taxonomic classification (Binzel et al 2001) and the Hayabusa data revealed an olivine-rich mineral assemblage silimar to LL5 or LL6 chondrites (Abe et al 2006;Okada et al 2006). Apophis is characterised as an Sq-type that most closely resembles LL ordinary chondrite meteorites (Binzel et al 2009).…”
Section: Discussionmentioning
confidence: 99%